1982
DOI: 10.1136/bmj.285.6349.1185
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of patients attending a diarrhoeal disease hospital in Bangladesh

Abstract: In October 1979 a surveillance system was set up at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
103
3

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(115 citation statements)
references
References 14 publications
9
103
3
Order By: Relevance
“…Dominance has been reported in some fatal cases (Butler et al, 1983). The 4% sampling system used in this study was found to be suitable for determining the seasonal pattern of various enteropathogens in a particular area (Stoll et al, 1982). In the present study, although the incidence of C. jejuni infection was slightly higher in cold months, it did not show any clear seasonal trend; the monthly rate of isolation was in the range 415% with an average of 7%.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Dominance has been reported in some fatal cases (Butler et al, 1983). The 4% sampling system used in this study was found to be suitable for determining the seasonal pattern of various enteropathogens in a particular area (Stoll et al, 1982). In the present study, although the incidence of C. jejuni infection was slightly higher in cold months, it did not show any clear seasonal trend; the monthly rate of isolation was in the range 415% with an average of 7%.…”
Section: Discussioncontrasting
confidence: 46%
“…On admission, the patient's physical condition, including the state of hydration, was determined by a doctor, and the patient's guardian was interviewed by a trained health assistant to obtain a standard medical history (Stoll et al, 1982). Weight and height were measured for assessment of nutritional status of patients under 10 years old by comparison with the Harvard Standard (Jelliffe, 1966).…”
Section: Isolation and Sources Of Strainsmentioning
confidence: 99%
“…Dehydration status was established according to standard World Health Organization criteria (WHO, 2005). Dehydration was considered moderate when estimated between 5-10 % and severe if .10 % (Stoll et al, 1982). The minimum community-based incidence rates of diarrhoea were estimated using the Rabat-Salé-Zemmour-Zair region population as described elsewhere (Kotloff et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The hospital has a longstanding Diarrheal Disease Surveillance system, 8 in which every 50th patient undergoes detailed questioning, a physical examination, and culture and analysis of stool. The surveillance system has been described previously in detail.…”
Section: Methodsmentioning
confidence: 99%
“…The surveillance system has been described previously in detail. 8 Using structured questions, trained personnel interview patients and/or their attendants to collect relevant information on symptoms, demographic and socioeconomic characteristics, housing and environmental conditions, feeding practices, and use of drugs and fluid therapy at home. All patients receive treatment according to the treatment guidelines of the hospital.…”
Section: Methodsmentioning
confidence: 99%